2012
DOI: 10.1038/oby.2011.141
|View full text |Cite
|
Sign up to set email alerts
|

The Women's Health Initiative: The Food Environment, Neighborhood Socioeconomic Status, BMI, and Blood Pressure

Abstract: Using data (n=60,775 women) from the Women’s Health Initiative Clinical Trial (WHI CT)— a national study of postmenopausal women aged 50 to 79 years — we analyzed cross-sectional associations between the availability of different types of food outlets in the 1.5 miles surrounding a woman’s residence, census tract neighborhood socioeconomic status (NSES), body mass index (BMI) and blood pressure (BP). We simultaneously modeled NSES and food outlets using linear and logistic regression models, adjusting for mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
121
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(130 citation statements)
references
References 36 publications
5
121
1
3
Order By: Relevance
“…Other studies have reported similar results concerning odds for hypertension with proximity to major roadway [15] and street foods [48]. One possible explanation apart from physical activity is that the availability of facilities within walkable distance provides access, for example, to retail fruits and vegetables.…”
Section: Discussionsupporting
confidence: 66%
“…Other studies have reported similar results concerning odds for hypertension with proximity to major roadway [15] and street foods [48]. One possible explanation apart from physical activity is that the availability of facilities within walkable distance provides access, for example, to retail fruits and vegetables.…”
Section: Discussionsupporting
confidence: 66%
“…As examples, better access to grocery stores or recreational facilities has been associated with lower average blood pressure levels in large studies. [4][5][6][7] High levels of neighborhood problems, such as crime, have been associated with higher blood pressure levels. 4,7,8 Conversely, neighborhood social cohesion, which is a sense of solidarity, has been associated with lower risk of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Availability of healthy food outlets and supermarkets have been inversely associated with BMI and obesity in some,5–8 but not all, studies 9 10. Access to fast food and all types of restaurants have been found to be associated with higher levels of BMI in some studies,5 11 but null and even inverse associations have also been reported 6 12 13. In general, neighbourhoods that are more unsafe or have lower levels of aesthetic quality have been linked to higher levels of BMI and obesity,14 15 whereas findings for other features of neighbourhood social environments, such as social cohesion and psychosocial hazards, have been more mixed 16 17…”
Section: Introductionmentioning
confidence: 99%